Challenges in the interpretation of a germline TERT variant in a patient with juvenile myelomonocytic leukemia. Issue 10 (4th August 2022) - Janczar, Szymon; Kirschner, Martin; Beier, Fabian; Brümmendorf, Tim H.; Ussowicz, Marek; Babol‐Pokora, Katarzyna; Oszer, Aleksandra; Yoshimi, Ayami; Kalwak, Krzysztof; Mlynarski, Wojciech
Abstract: Dyskeratosis congenita (DC) is a bone marrow failure syndrome with extrahematopoietic abnormalities. DC is a paradigmatic telomere biology disorder (TBD) caused by germline mutations in genes responsible for telomere maintenance including TERT . Cryptic TBD is a bone marrow failure syndrome due to premature telomere shortening but without additional symptoms, frequently clinically indistinguishable from severe aplastic anemia (SAA) or hypoplastic myelodysplastic syndrome. We present the complex diagnostic pathway in a boy with a rare germline p.Thr726Met TERT variant with previous reports of SAA association and compromised enzymatic function who presented with juvenile myelomonocytic leukemia, which is a rare myelodysplastic/myeloproliferative neoplasm of childhood.